APORIAS OF THE MODERN METAPHYSICAL CRITICISM OF RELIGION IN LEO STRAUSS’S EARLY INTERPRETATION OF SPINOZA’S THEOLOGICO-POLITICAL TREATISE - Ciccarelli, Pierpaolo (Science et Esprit, 2024)
In this paper I first (§ 2) examine the metacriticism of modern critique of religion that Strauss formulates in his first book on Spinoza (1930). According to this early interpretation by Strauss, Spinoza undertakes a metaphysical critique of religion in order to confute the ontological possibility of divine revelation (or ‘miracle thesis’). Spinoza’s attempt, however, ends in an aporia: the ultimate presupposition underlying belief in revelation remains irrefutable. In the § 3 I examine a text published by Strauss shortly afterwards (1935), in which I detect a self-critique of his earlier meta-criticism of modern critique of religion. Strauss become aware here that his own understanding of Spinoza’s aporia is itself aporetic. It is in this aporia, in my view, that we must look for the key to understanding what Strauss would call retrospectively (1962) his own ‘change of orientation’ and, consequently, his discovery of ‘philosophical exotericism.’